Implementasi Handout Dinamika Rotasi Berbantuan Metode Eliminasi Gauss-Jordan Terhadap Kemampuan Berpikir Matematis dan Hasil Belajar Murid - Aulia Wulansari Agustin (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine whether there is a significant difference in mathematical thinking abilities and learning outcomes between students who use handouts on rotational dynamics assisted by the Gauss-Jordan elimination method and those who use handouts assisted by the substitution and elimination method. This study used a quasi-experimental quantitative approach with a Posttest-Only Control Group Design at SMAN 3 Jember, where the control class was given handouts using the substitution and elimination methods, and the experimental class was given handouts using the Gauss-Jordan elimination method. Data analysis was performed using a non-parametric test through the Mann-Whitney test. The results showed a significant difference in mathematical thinking ability between the control class and the experimental class with an Asymp.Sig. (2-tailed) value of 0.000 < 0.05. In addition, student learning outcomes also showed a significant difference between the two sample classes with an Asymp.Sig. (2-tailed) value of 0.005 < 0.05. These findings indicate that the use of handouts assisted by the Gauss-Jordan elimination method can help students organize their solution steps in a more structured and systematic manner when solving rotational dynamics problems in pulley systems.
:: Finalisasi Repositori File 25 Mei 2026_Kurnadi
Keywords: mathematical thinking ability; learning outcomes; Gauss-Jordan elimination